2022
DOI: 10.1101/2022.03.02.22271552
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A predictive model for hospitalization and survival to COVID-19 in a retrospective population-based study

Abstract: The severe acute respiratory syndrome coronavirus (SARS-CoV-2) causing coronavirus disease 2019 (COVID-19) is highly transmissible and has been responsible for a pandemic associated with a high number of deaths. The clinical management of patients and the optimal use of resources are two important factors in reducing this mortality, especially in scenarios of high incidence. To this end, it is necessary to develop tools that allow early triage of patients with the minimal use of diagnostic tests and based on r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…The results of Khozeimeh et al's 58 study also showed that one of the most important features related to the mortality of patients with COVID-19 was heart disease. The results of studies of Ahmed et al 54 and Cisterna-García et al 56 similar to the results of our study, identified the features of lung disease, blood pressure, and acute respiratory distress syndrome as effective factors in the development of a predictive survival system.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results of Khozeimeh et al's 58 study also showed that one of the most important features related to the mortality of patients with COVID-19 was heart disease. The results of studies of Ahmed et al 54 and Cisterna-García et al 56 similar to the results of our study, identified the features of lung disease, blood pressure, and acute respiratory distress syndrome as effective factors in the development of a predictive survival system.…”
Section: Discussionsupporting
confidence: 91%
“…data set. 53 Various studies [54][55][56][57][58][59][60][61] were conducted in predicting the survival and mortality of COVID-19 patients using ML techniques. Krajah's et al 59 study showed intubation was the most important features for the survival prediction.…”
Section: Nb Classifier Can Classify All the Cases Of Death Correctly ...mentioning
confidence: 99%
“…Currently available COVID-19 risk prediction models have important limitations. First, most models were developed early in the pandemic (8)(9)(10)(11)(12)(13) and do not account for current circulating viral strains, population immunity from previous infection or vaccination, and treatments. This is particularly important as risk models are sensitive to population contextual factors under which they are developed.…”
Section: Introductionmentioning
confidence: 99%